Synthesis and Evaluation of Some Coumarin Containing Potential Antimicrobial Agents - Sayali D. Kudale; Meenakshi N. Deodhar (E-Journal of Chemistry)
A series of the Schiff’s bases incorporating coumarin and chalcone moeities, 3-(4-(4-(substituted phenyl)prop-1-ene-3-one) phenylimino) methyl)-4-chloro-2h-chromen-2-one 4(a-g) were synthesized as potential antimicrobial agents. These compounds were characterized on the basis of their spectral (IR, 1H NMR) data and evaluated for antimicrobial activity in vitro against gram positive and gram negative bacteria and fungi. Compound 4b was found to be most active with an MIC of 20 µg/mL against all the tested organisms.